2018
DOI: 10.1155/2018/6030646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Restricted Diet Administered during Perinatal and Postnatal Periods on the Penis of Wistar Rats

Abstract: Vitamin D deficiency is common in pregnant women and infants. The present study aimed to investigate the effects of vitamin D restricted diet on the Wistar rats offspring penis morphology. Mother rats received either standard diet (SC) or vitamin D restricted (VitD) diet. At birth, offspring were divided into SC/SC (from SC mothers, fed with SC diet) and VitD/VitD (from VitD mothers, fed with VitD diet). After euthanasia the penises were processed for histomorphometric analysis. The VitD/VitD offspring display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…There are many risk factors in the etiology of ED which might be directly arising from VDD. Since the latest literature showed the importance of VD on erectile function, Fernandes-Lima et al [ 34 ] investigated the effects of VD restricted diet on Wistar rats offspring penis morphology. Fernandes-Lima et al [ 34 ] demonstrated that VD restriction during perinatal and postnatal periods induced metabolic and structural changes and represented important risk factors for ED in the penis of the adult offspring.…”
Section: Vitamin-d and Erectile Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many risk factors in the etiology of ED which might be directly arising from VDD. Since the latest literature showed the importance of VD on erectile function, Fernandes-Lima et al [ 34 ] investigated the effects of VD restricted diet on Wistar rats offspring penis morphology. Fernandes-Lima et al [ 34 ] demonstrated that VD restriction during perinatal and postnatal periods induced metabolic and structural changes and represented important risk factors for ED in the penis of the adult offspring.…”
Section: Vitamin-d and Erectile Dysfunctionmentioning
confidence: 99%
“…Since the latest literature showed the importance of VD on erectile function, Fernandes-Lima et al [ 34 ] investigated the effects of VD restricted diet on Wistar rats offspring penis morphology. Fernandes-Lima et al [ 34 ] demonstrated that VD restriction during perinatal and postnatal periods induced metabolic and structural changes and represented important risk factors for ED in the penis of the adult offspring. The latter findings suggest that VD is an important micronutrient in maintaining the cytoarchitecture of the penis [ 34 ].…”
Section: Vitamin-d and Erectile Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D plays an important role in endothelial system health by providing blood pressure regulation through suppression of renin and also with direct effects such as anti-oxidative and anti-inflammatory [5][6][7][8]. It also plays an important role in providing an intact penis anatomy and histology and in the synthesis of nitric oxide, which is necessary in physiology of erection [6,9,10]. In addition, it is hypothesized that vitamin D may have an effect on the improvement of erectile function (EF) by its affinity on testosterone receptors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Serum vitamin D levels have an important function on calcium homoeostasis and bone metabolism. Accordingly, serum vitamin D levels are associated with calcifications of some soft tissues (Abedin, Tintut, & Demer, ; Fernandes‐Lima et al, ). The current molecular studies presented that Vitamin D increases the expression of TGF‐β1 and induces T‐cell differentiation by regulating the TGF‐β1 pathway (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%